2021
DOI: 10.1111/bjh.17975
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen gradient ektacytometry does not predict pain in children with sickle cell anaemia

Abstract: The loss of red blood cell (RBC) deformability in sickle cell anaemia (SCA) is considered the primary factor responsible for episodes of acute pain and downstream progressive organ dysfunction. Oxygen gradient ektacytometry (Oxygenscan) is a recently commercialised functional assay that aims to describe the deformability of RBCs in SCA at differing oxygen tensions. So far, the Oxygenscan has been evaluated only by a small number of research groups and the validity and clinical value of Oxygenscan-derived bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…In another study, Rab et al showed the impact of the time from blood sampling to measurement, the amount of RBCs during testing, the camera gain settings, and the speed of deoxygenation on the measurements of oxygen gradient ektacytometry and therefore concluded that the standardization of oxygen gradient ektacytometry would allow different laboratories to compare RBC rheology study in SCD ( Rab et al, 2020 ). Moreover, a recent study by Nardo-Marino et al showed that oxygen gradient ektacytometry measurements correlate with key hematological parameters in children with SCD such as Hb levels, HbF, lactate dehydrogenase, and reticulocyte counts ( Nardo-Marino et al, 2021 ). However, this study challenges oxygen gradient ektacytometry that it failed to detect the effect of hydroxyurea (HU) treatment and pain level in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Rab et al showed the impact of the time from blood sampling to measurement, the amount of RBCs during testing, the camera gain settings, and the speed of deoxygenation on the measurements of oxygen gradient ektacytometry and therefore concluded that the standardization of oxygen gradient ektacytometry would allow different laboratories to compare RBC rheology study in SCD ( Rab et al, 2020 ). Moreover, a recent study by Nardo-Marino et al showed that oxygen gradient ektacytometry measurements correlate with key hematological parameters in children with SCD such as Hb levels, HbF, lactate dehydrogenase, and reticulocyte counts ( Nardo-Marino et al, 2021 ). However, this study challenges oxygen gradient ektacytometry that it failed to detect the effect of hydroxyurea (HU) treatment and pain level in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies show that the various ektacytometry parameters correlate with many factors in SCD, such as total hemoglobin and HbF percentage, there is nothing to suggest that this approach offers any additional or independent prognostic information. 44 …”
Section: Can We Identify Prognostic Groups In Sickle Cell Disease?mentioning
confidence: 99%
“…7 The mean (SD) HbS and HbF percentages were 82.6 (9.0)% and 13.3 (9.2)%, respectively. The mean (SD) Hb, Hct, MCV and MCHC values were 87 (15) g/l, 27.0 (5.3)%, 83 (13) fl and 343 (15) g/l, respectively. The mean (SD) P50 and PoS values were 29.3 (3.8) mmHg and 44.2 (9.5) mmHg, respectively.…”
mentioning
confidence: 95%
“…Rab et al 2 demonstrated that the PoS was higher in both adults and children with SCA with frequent vaso-occlusive crises compared to those with few crises. However, a recent study did not find such a relationship, 13 re-enforcing the need to conduct very large multicentric studies to assess the clinical usefulness of oxygenscan. Oxygenscan is useful to test the biological efficacy of various molecules.…”
mentioning
confidence: 99%